Efektifitas, Perkembangan Psikom EFEKTIFITAS PEMBELAJARAN ONLINE TERHADAP PERKEMBANGAN PSIKOMOTORIK ANAK USIA DINI - DESIKA PUTRI MARDIANI (Jurnal Paradigma, 2022)
The Covid-19 pandemic still has an impact on various fields of people's lives, especially in the field of education. Several educational institutions, such as Early Childhood Education and Kindergarten schools, are still implementing online learning in carrying out teaching and learning activities as an effort to prevent the spread of the Covid-19 virus. The online learning system is new and is still in the habituation stage for some people, while early childhood requires sufficient stimulation through direct or face-to-face learning to maximize the stimulation process. However, educators and parents are faced with a period: even though the learning system is implemented online, the target for learning outcomes must also be achieved, one of which is the achievement of the psychomotor development target of early childhood. This study aims to determine the percentage of the effectiveness of online learning on the psychomotor development of early childhood. The research location is in RA Roudhotul Ulum which is located in Baluk Village, Karangrejo District, Magetan Regency. The research was carried out on March 5, 2020 – April 30, 2020. The research approach used was descriptive quantitative with data collection techniques utilizing online questionnaires from Google Forms which were distributed to educators and parents, with a total of 45 respondents. The results of this study are that online learning is considered less effective in achieving psychomotor development in early childhood which is influenced by various factors. Almost all respondents want to immediately implement offline or face-to-face learning, so that the achievement of children's development targets can be realized to the fullest. Keywords: Effectiveness, Psychomotor Development, Early Childhood